Internal Control, Autonomy, and Competence in Village Financial Management: Pengendalian Internal, Otonomi, dan Kompetensi dalam Pengelolaan Keuangan Desa - Amilliyah, Winda Ayu; Biduri, Sarwendah (Indonesian Journal of Law and Economics Review, 2025)
Background: Village financial management has become a key issue in improving transparency and accountability in Indonesia’s local governance. Specific Background: The implementation of Law No. 20 of 2018 requires villages to manage finances effectively through strong internal control, regional autonomy, and competent human resources. Gap: Previous studies mostly analyzed these variables separately without integrating them into one model. Aim: This study investigates how internal control systems, regional autonomy, and village apparatus competence relate to village financial management. Results: Using a quantitative approach with multiple regression analysis, findings show that all three variables significantly contribute to improving financial management performance, explaining 62.9% of its variation. Novelty: The study integrates regulatory, organizational, and human resource aspects into one analytical framework. Implications: Strengthening internal control and enhancing competence are crucial to improve governance quality at the village level. Highlights:• Internal control strengthens village financial accountability• Autonomy improves governance independence• Competence enhances financial management quality Keywords: Internal Control, Regional Autonomy, Competence, Village Finance, Governance